One Stop Learning Innovation Rumah Kedelai Grobogan as an Effort to Strengthen Indonesia's Food Security - Prastikawati, Nevelona (Universitas Airlangga, 2024)
Abstract The objective of this paper is to analyze the 'One Stop Learning' innovation at Rumah Kedelai Grobogan (RKG) and its impact on strengthening food security in Indonesia, considering the high national demand for soybeans and the dependency on imports. This research employs a qualitative approach with a case study method, incorporating secondary data analysis, stakeholder interviews, and field observations. The findings reveal that the 'One Stop Learning' innovation at RKG has significantly boosted local soybean production from 10,709 tons in 2020 to 34,603 tons in 2022. Additionally, this innovation has fostered the growth of small and medium enterprises involved in tofu and tempeh production and increased the number of soybean seed breeders. The study is limited to data from Grobogan Regency and may not be generalizable to other regions in Indonesia with different agricultural conditions. Future research could explore multiple regions and use a longitudinal approach to assess long-term impacts. The practical implications of the 'One Stop Learning' model at RKG provide a replicable framework for other regions in Indonesia to enhance local soybean production and reduce reliance on genetically modified imported soybeans. This model also promotes an integrated agribusiness ecosystem from upstream to downstream processes. This study offers insights into how integrated educational and innovative approaches in agribusiness can strengthen national food security, with the 'One Stop Learning' approach supporting national food security. Keywords: innovation, one stop learning, food security, rumah kedelai grobogan, local soybean production. Abstrak Tujuan dari makalah ini adalah menganalisis inovasi 'One Stop Learning' di Rumah Kedelai Grobogan (RKG) terhadap penguatan ketahanan pangan di Indonesia, mengingat tingginya permintaan nasional akan kedelai dan ketergantungan pada impor. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus, menggabungkan analisis data sekunder, wawancara dengan pemangku kepentingan, dan observasi lapangan. Temuan menunjukkan bahwa inovasi 'One Stop Learning' di RKG secara signifikan meningkatkan produksi kedelai lokal dari 10.709 ton pada tahun 2020 menjadi 34.603 ton pada tahun 2022. Selain itu, inovasi ini telah mendorong pertumbuhan usaha kecil dan menengah yang terlibat dalam produksi tahu dan tempe, serta meningkatkan jumlah penangkar benih kedelai. Penelitian ini terbatas pada data dari Kabupaten Grobogan dan mungkin tidak dapat digeneralisasikan ke daerah lain di Indonesia dengan kondisi pertanian yang berbeda. Penelitian selanjutnya dapat mengeksplorasi beberapa wilayah dan menggunakan pendekatan longitudinal untuk menilai dampak jangka panjang. Implikasi Praktis model 'One Stop Learning' di RKG menyediakan kerangka kerja yang dapat direplikasi oleh daerah lain di Indonesia untuk meningkatkan produksi kedelai lokal dan mengurangi ketergantungan pada kedelai impor yang dimodifikasi secara genetik. Model ini juga mendorong ekosistem agribisnis yang terintegrasi dari proses hulu ke hilir. Studi ini menawarkan wawasan tentang pendekatan pendidikan dan inovasi yang terintegrasi dalam agribisnis dapat memperkuat ketahanan pangan nasional pendekatan 'One Stop Learning' mendukung ketahanan pangan nasional Kata kunci: inovasi, one stop learning, ketahanan pangan, rumah kedelai grobogan, produksi kedelai lokal.